2019
DOI: 10.1111/ajt.15416
|View full text |Cite
|
Sign up to set email alerts
|

Absolute quantification of donor-derived cell-free DNA as a marker of rejection and graft injury in kidney transplantation: Results from a prospective observational study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.Donor-derived cell-free DNA (dd-cfDNA) is a noninvasive biomarker for comprehensive monitoring of allograft injury and rejection in kidney transplantation (KTx). dd-cfDNA quantification of copies/mL plasma (dd-cfDNA[cp/mL]) was compared to dd-cfDNA fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
220
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(232 citation statements)
references
References 39 publications
10
220
0
2
Order By: Relevance
“…Fourth, detection timing will also affect the results. Evidence has confirmed that cfDNA will increase early in the postoperative period, and about 5 days after the will operation, cfDNA decrease to the normal value (23). If the ischemia-reperfusion injury is serious, the cfDNA will decline more slowly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, detection timing will also affect the results. Evidence has confirmed that cfDNA will increase early in the postoperative period, and about 5 days after the will operation, cfDNA decrease to the normal value (23). If the ischemia-reperfusion injury is serious, the cfDNA will decline more slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (25) supported this conclusion and demonstrated that cfDNA fraction was higher in ABMR compared with TCMR while cfDNA fraction was not able to discriminate TCMR from no rejection. However, Oellerich et al (23) and Sigdel et al (24) showed that cfDNA fraction increased in either ABMR or TCMR and it was unable to discriminate them. More studies with large sample size were needed to solve the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Although renal allograft biopsies are generally considered to be safe, it is associated with risks such as bleeding, hematoma, and AVM formations. Liquid biopsy obtained by measurement of dd-cfDNA can serve as an alternative to the invasive renal allograft biopsy and has evolved to a frequently used tool for surveillance and diagnosing of KT rejection, as well as monitoring of therapy 3,8,10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The donor allele remained below 0.5% or 50 copies/mL in stable patients, while a significant increase was observed on graft injury. What is noteworthy, the authors implemented xenogeneic spike-in to the isolation protocol, thus accounting for isolation efficiency to accurately quantify absolute ddcfDNA levels 17. A high throughput clinical trial investigating the possibility to monitor heart transplant rejection with liquid biopsy was performed by De Vlaminck et al 11.…”
Section: Discussionmentioning
confidence: 99%